Implementation of Graduate Competency Standards (SKL) in Nonformal Education Programs: A Case Study of Sewing Skills Training at Joenita Modiste - Nayla Nanda Friadi; Rahmat Fahmi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Graduate Competency Standards (Standar Kompetensi Lulusan/SKL) constitute one of the eight National Education Standards that serve as a benchmark for the quality of educational implementation in Indonesia, including nonformal education. This article aims to examine the implementation of SKL in vocational skill-based nonformal education programs using empirical data from the Performance Evaluation Report of the Sewing Skills Training Program at Joenita Modiste. Data were collected through method triangulation, including semi-structured interviews, direct observation, and documentation studies. The findings indicate that the three dimensions of SKL—attitudes, knowledge, and skills—can be effectively implemented in vocational nonformal education programs. This is reflected in the participants’ consistent attendance driven by intrinsic motivation, mastery of sewing techniques from beginner to advanced levels, product quality that meets institutional standards, and economic impacts in the form of business opportunities for participants within three months after training completion. These findings confirm that SKL is an applicable and measurable quality framework for competency-based nonformal education programs.